Human Trafficking Crime Networks and Pastoral Efforts for Prevention - Herman Punda Panda (Sekolah Tinggi Teologi Intheos Surakarta, 2021)
Human trafficking is human exploitation, and it contradicts the biblical message which encourages equal and harmonious relationships between humans. Therefore, efforts needed for prevention. This study aimed to expose the criminal network of trafficking in persons specifically from Southwest Sumba Regency where Malaysia is a destination country. Data analysis based on Holland and Henriot model of the pastoral circle. The method used was descriptive qualitative. Data were obtained through observation, interviews, and literature studies, which were analyzed in depth. The result was that an effective pastoral action to prevent human trafficking is based on a deep understanding of trafficking in persons with adequate theological reflection.